The Effect of Training Method and Leg Length on The Vertical Jump Result in The Volleyball Maras Bangka Club Athlete (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the effect of maxex training methods and depth jump exercises and leg length on the vertical jump results in the volleyball athletes of the Maras Bangka club. This research is a quasi-experimental research with a 2x2 factorial design of 20 research samples with a sampling technique using a purposive sampling technique. An instrument of this study was the length of the legs measured by the meter and the results of the vertical jump with the vertical jump test. Data analysis techniques used Analysis of Variance (ANOVA) with SPSS 24 program. The results of this study there is a difference in effect between maxex training and depth jump on the results of vertical jumps in the Maras Bangka club volleyball athletes, there is a difference in the effect of long and short limb lengths on the vertical jump results in the volleyball athletes of the Maras Bangka club, there is an interaction between the training methods and leg length on the vertical jump results in the volleyball athlete Maras Bangka club. The conclusion is that there is an influence between the exercise method and leg length on the vertical jump results in the volleyball athlete Maras Bangka club. Suggestions for the Maras Bangka club, physical conditions need to be considered for achieving optimal results and need to develop more effective and appropriate training programs.